2017
DOI: 10.7554/elife.21776
|View full text |Cite
|
Sign up to set email alerts
|

Impaired retrograde transport of axonal autophagosomes contributes to autophagic stress in Alzheimer’s disease neurons

Abstract: Neurons face unique challenges of transporting nascent autophagic vacuoles (AVs) from distal axons toward the soma, where mature lysosomes are mainly located. Autophagy defects have been linked to Alzheimer’s disease (AD). However, the mechanisms underlying altered autophagy remain unknown. Here, we demonstrate that defective retrograde transport contributes to autophagic stress in AD axons. Amphisomes predominantly accumulate at axonal terminals of mutant hAPP mice and AD patient brains. Amyloid-β (Aβ) oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 81 publications
4
110
0
1
Order By: Relevance
“…Misfolded proteins generated in axons and dendrites are retrogradely transported to the lysosome-rich microtubule-organizing center (MTOC). In MTOC, they are packed into aggresomes, and subsequently degraded in the lysosome [47,48]. These functions are regulated by histone deacetylase-6 (HDAC6).…”
Section: Role Of Hdac6 In Aggrephagymentioning
confidence: 99%
See 2 more Smart Citations
“…Misfolded proteins generated in axons and dendrites are retrogradely transported to the lysosome-rich microtubule-organizing center (MTOC). In MTOC, they are packed into aggresomes, and subsequently degraded in the lysosome [47,48]. These functions are regulated by histone deacetylase-6 (HDAC6).…”
Section: Role Of Hdac6 In Aggrephagymentioning
confidence: 99%
“…This complex is necessary for the fast axonal transport of aggregates and autophagy vacuoles to the perinuclear space for lysosomal degradation [86]. Impairment in their axonal transportation affects their lysosomal degradation [47]. Moreover, this impairment increases the aggregates level in neuronal axons and synapses.…”
Section: Dysregulation In Aggregates Retrograde Transport In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in autophagic flux (Lumkwana et al, 2017;Menzies et al, 2017;Nixon, 2013), AV transport (Tammineni et al, 2017), and lysosomal function (Gowrishankar et al, 2015;Lee et al, 2011aLee et al, , 2011b have been implicated in various neurodegenerative diseases. Furthermore, previous studies have identified mutations in organelle transport machinery that are linked to neurodegenerative disease (Maday et al, 2012;Millecamps and Julien, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given their distance from the cell soma and high metabolic demand, synapses poise a significant challenge to neurons, as they have to maintain and ensure a stable functional pool of proteins (Tammineni et al, 2017). How might this be achieved?…”
Section: Introductionmentioning
confidence: 99%